Effects of Edible Treats Containing Ascophyllum nodosum on the Oral Health of Dogs: A Double-Blind, Randomized, Placebo-Controlled Single-Center Study - Gawor, Jerzy; Jank, Michał; Jodkowska, Katarzyna; Klim, Emilia; Svensson, Ulla K. (Frontiers in Veterinary Science, 2018)
The objective of this placebo-controlled, double-blind, randomized study (designed according to evidence based medicine standards) was to determine the effect of 90-day administration of edible treats containing the brown algae, Ascophyllum nodosum, on plaque and dental calculus accumulation on the teeth of dogs, as well as on other parameters characterizing canine oral health status, including: plaque index (PI), calculus index (CI), oral health index (OHI), gingival bleeding index (GBI), and volatile sulfur compound (VSC) concentration. Sixty client-owned dogs, including Japanese chin, miniature Schnauzer, Chihuahua, Pomeranian, and West Highland White Terrier (WHWT) breeds, underwent professional dental cleaning and were randomly subdivided into two groups receiving daily edible treats containing the brown algae A. nodosum, or placebo, adjusted to their bodyweight. After a comprehensive oral health assessment, including a professional dental cleaning, which were both performed under general anesthesia, clinical assessments of PI, CI, OHI, GBI, and VSC concentration were performed under sedation after 30, 60, and 90 days of treatment. Oral administration of edible treats containing A. nodosum significantly improved PI, CI, and VSC concentration, compared with the placebo-treated group. The consumption of edible treats containing A. nodosum efficiently decreased plaque and calculus accumulation in the investigated dogs. Dogs treated with A. nodosum also exhibited significantly lower concentrations of VSC and better oral health status (e.g., OHI and GBI) than those in the placebo-control group.